Microsoft Teams for dummies - Withee, Rosemarie (--For dummies., 2020)
Discover the power of Microsoft Teams Millions of people access Microsoft Teams every day to assist with the collaboration it takes to get work done. That number continues to grow thanks to the countless communication tools for working with associates inside and outside your organization you can find in Microsoft Teams. If you're new to Microsoft Teams, start here. This book will give you must-have insight on chatting, file sharing, organizing teams, using video communication, and more. You'll also see just how you should be doing things, with best-practice recommendations and ideas for integrating Microsoft Teams into your existing workflows. Learn your way around Microsoft Teams and set up the interface; Communicate via chat and video chat, inside and outside your org; Integrate Teams with other Office apps for seamless collaboration; Use Teams to optimize your meetings, build a knowledge wiki, and more!